A systematic review of zirconia as an implant material - D R Prithviraj; S Deeksha; K M Regish; N Anoop (Wolters Kluwer Medknow Publications, 2012)
The purpose of this systematic review was to assess the published data concerning zirconia dental implants from various aspects. To identify relevant literature an electronic search was performed of PubMed. Titles and abstracts were screened and articles that fulfilled the inclusion criteria were selected for a full-text reading. Articles were divided into four groups: 1) studies evaluating the mechanical properties of zirconia implants, 2) studies on osseointegration of zirconia, 3) studies on peri-implant tissue response to zirconia implant, and 4) studies on plaque accumulation with zirconia. Review of the selected articles showed that zirconia implants are reliable for placement in the jaw bone. Furthermore, zirconia implants present a material surface that is compatible with the peri-implant tissue and relatively less attractive to plaque. Based on the reviewed literature, it appears that zirconia has the potential to become the dental implant material of choice, especially for aesthetic restorations; however, some issues need to be studied further.